Analytical Models for Optimal Design of a Trapezoidal Composite Channel Cross-Section - Pourbakhshian, Somayyeh; Pouraminian, Majid (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper, several analytical models are presented for the optimal design of a trapezoidal composite channel cross-section. The objective function is the cost function per unit length of the channel, which includes the excavation and lining costs. To define the system, design variables including channel depth, channel width, side slopes, freeboard, and roughness coefficients were used. The constraints include Manning`s equation, flow velocity, Froude number, and water surface width. The Simultaneous Perturbation Stochastic Approximation (SPSA) algorithm was used to solve the optimization problem.
Keywords: trapezoidal composite channel; optimal design; analytical models; SPSA algorithm; kanał trapezowy; koszt wykopu; projekt optymalny; model analityczny; algorytm SPSA